The unfinished agenda: perspectives on overcoming hunger, poverty, and environmental degradation - Pinstrup-Andersen, Per; Pandya-Lorch, Rajul (International Food Policy Research Institute, 2001)
This book brings together briefs and articles generated by the 2020 Vision initiative that remain highly relevant to the ongoing dialog and debate and, given the nature of the topics addressed, are likely to remain so for some time to come.